Doctors' willingness to give honest answers about end-of-life practices: a cross-sectional study. Issue 5 (22nd May 2013) - Merry, Alan F; Moharib, Magdi; Devcich, Daniel A; Webster, M Louise; Ives, Jonathan; Draper, Heather
Abstract : Objectives: We aimed to (1) evaluate the extent to which doctors in New Zealand would be willing to answer honestly questions about their care of patients at the end of their lives and (2) identify the assurances that would encourage this. Results were compared with findings from a previous pilot study from the UK. Design: Survey study involving a mailed questionnaire. Setting: New Zealand hospital and community-based medical care settings. Participants: The questionnaire was mailed to a random sample of 800 doctors in New Zealand who were vocationally registered with the Medical Council of New Zealand in disciplines involving caring for patients at the end of their lives. Primary and secondary outcome measures: Willingness to provide honest answers about various aspects of end-of-life care; assurances that might increase willingness to provide honest answers to questions about end-of-life practices. Results: Completed questionnaires were returned by 436 doctors. The majority of respondents (59.9–91.5%) indicated willingness to provide honest answers to such questions. However, more than a third of doctors were unwilling to give honest answers to certain questions regarding euthanasia. These results are comparable with the UK data. Complete anonymity was the assurance most likely to encourage honest answering, with most of the respondents preferring the use of anonymous written replies. Respondents were less reassured by survey endorsements from regulatory bodies. Themes in free comments included the deterrent effect of medicolegal consequences, fear of censure from society, peers and the media and concerns about the motivations and potential uses of such research. Conclusions: Many New Zealand doctors were willing to give honest answers to questions about end-of-life practices, particularly if anonymity was guaranteed; others, however, expressed doubts or indicated that they would not be willing to provide honest answers to questions of this sort.